EU cohesion policy and European integration the dynamics of EU budget and regional policy reform - Bachtler, John; Mendez, Carlos; Wishlade, Fiona (Routledge is an imprint of the Taylor & Francis Group, an informa business, 2014)
This book provides a comprehensive and theoretically-informed analysis of how Cohesion policy has evolved over time, in particular the budgetary and policy dynamics of the 2007-13 reform. In the context of the budgetary politics of the EU, the book examines the process by which the reform of Cohesion policy has been shaped; it identifies the key factors that explain the allocation of funding, assesses the roles of the Member States, European Commission and European Parliament, and tests whether the process and outcome are consistent with the expectations of EU decision-making and integration theories